2014
DOI: 10.1155/2014/954045
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Epicardial Adipose Tissue Thickness and Oxidative Stress Parameters in Isolated Metabolic Syndrome Patients: A Multimarker Approach

Abstract: The risk for cardiovascular diseases and type 2 diabetes mellitus significantly increases in the patient population with metabolic syndrome (MeS). The present study aimed to investigate the association between the epicardial adipose tissue thickness (EATT) and the oxidative stress parameters in MeS patients. The study included 181 patients as a patient group of 92 consecutive patients with MeS and a control group of 89 consecutive patients with similar age and gender. EATT was evaluated by transthoracic echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Our results demonstrated an increase in the lipid peroxidation in the hypercaloric diet group, which could be due to an elevated production of reactive oxygen species (ROS), an important condition for the development of metabolic syndrome and some disorders such obesity, systemic arterial hypertension (SAH), atherosclerosis, and diabetes [53,54]. However, an increase in the plasma TBARS was prevented by the CI extract or simvastatin treatments.…”
Section: Discussionmentioning
confidence: 72%
“…Our results demonstrated an increase in the lipid peroxidation in the hypercaloric diet group, which could be due to an elevated production of reactive oxygen species (ROS), an important condition for the development of metabolic syndrome and some disorders such obesity, systemic arterial hypertension (SAH), atherosclerosis, and diabetes [53,54]. However, an increase in the plasma TBARS was prevented by the CI extract or simvastatin treatments.…”
Section: Discussionmentioning
confidence: 72%
“…Epicardial adiposity has more markers of oxidative stress than subcutaneous fat tissue [30]. In patients with metabolic syndrome EFTT was associated with systemic oxidative stress [31] and is supposed to play a more important role in the stimulation of systemic oxidative stress than subcutaneous fat tissue. Another possible link between GGT activity and EFTT is insulin resistance which has been previously associated with both, higher levels of GGT [32,33] and increased amount of epicardial fat [22].…”
Section: Resultsmentioning
confidence: 99%
“…PCOS is a low-grade chronic inflammatory disease. Many studies have shown a relationship between PCOS and inflammation markers [7,8,26]. There is also a relationship between NRG4 and chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…In general, insulin resistance and hyperinsulinemia affect 70 percent of women with PCOS. Despite extensive research, the underlying mechanism of insulin resistance in PCOS has not been fully understood [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%